Using participatory visual research to explore resilience with girls and young women in rural South Africa. Issue 2 (3rd April 2017) - Wiebesiek, Lisa; Treffry-Goatley, Astrid
Abstract: Sexual violence is deeply embedded in historical and structural inequalities and is driven by unequal gender power relations. These unequal power relations give rise to gendered norms and practices that inform the social ecologies in which women and girls negotiate their lives. South Africa has one of the highest rates of sexual assault in the world. Research suggests that girls and women from resource-poor rural communities are particularly susceptible to sexual violence due to the dominance of gendered cultural practices and belief systems in these contexts. Our research is part of a six-year, international and interdisciplinary partnership which seeks to explore how participatory visual methods can be used to advance knowledge-production, policy-making and communication in relation to sexual violence against indigenous girls and young women in Canada and South Africa. The data presented in this article are drawn from a series of participatory visual workshops with girls and young women in rural KwaZulu-Natal, South Africa. Through a thematic analysis of girl-authored cellphilms and digital stories, and with reference to the seven qualitative aspects related to resilience (Ungar et al ., 2007), we explore two questions: (1) How do gendered power dynamics affect resilience in relation to sexual violence in their lives? (2) What is the relationship between resilience and the gendered nature of adversity in this setting? We conclude by suggesting how our work with the girls might support, build and leverage gender-specific resources, which could facilitate resilience in this environment.